MODIFIKASI DAN KARAKTERISASI ZEOLIT ALAM TASIKMALAYA DENGAN Fe2O3 - Oktaviani, Reka; Hindryawati, Noor; Panggabean, Aman Sentosa (JURNAL ATOMIK, 2019)
Research on natural zeolite has been carried out as a porous material modified by Fe 2 O 3 semiconductor material. Starting with natural zeolite preparation, dealumination by activating it using HCl solution, modifying natural zeolite with Fe 2 O 3 using FeCl 3 and NaOH solution, then characterized using X-Ray Fluorescence (XRF), X-Ray Diffraction (XRD), Scanning Electron Microscopy (SEM) and test the surface area using a Methylene Blue solution. The results of the XRF analysis showed that the composition of Fe 2 O 3 increased after it was modified to 38.022%, which was previously namely 3.193%. The results of SEM analysis showed changes in the morphology of natural zeolites after being modified with Fe 2 O 3 . The results of the XRD analysis showed that there was a diffraction peak which provided information that the sample contained Fe 2 O 3 . Zeolite-Fe 2 O 3 has a surface area of ??110,2707 m 2 /g.  Keywords : natural zeolite, Fe 2 O 3 , semiconduktor